From Decent Work to Decent Lives: An Empirical Test of the Outcomes of Decent Work in the Psychology of Working Theory - Malan, Danielle (Organisational Psychology, 2020)
The psychology of working theory (PWT) postulates that certain contextual and structural factors determine if individuals are able to obtain decent work, and that decent work, in turn, leads to work fulfilment and general well-being. The theory assumes that this is the case, as decent work satisfies three fundamental human needs: survival and power, social connection, and self-determination (as per the self-determination theory [SDT]). Only recently has a measure been developed to assess the satisfaction of these needs (Autin et al., under review), which means that the proposed role of need satisfaction as mediator in the link between decent work and work fulfilment/general well-being has not yet been tested empirically. This formed the objective of this study. The study employed a descriptive research design with a correlational approach. Working individuals residing in South Africa’s Western Cape province (N = 150) rated their work experiences on the decent work scale (DWS), work need satisfaction scale (WNSS), index of job satisfaction (IoJS) scale, and satisfaction with life scale (SWLS). In this sample, adequate healthcare did not fall within the decent work concept. This might be because it is common for working South Africans, especially in lower income brackets, not to receive healthcare benefits, which would thus not be expected. The autonomy and relationship aspects of the SDT self-determination need formed one instead of two separate components. This may be a reflection of low levels of trust in low-income workers, which means that autonomy is only provided if there is a positive relationship. Decent work predicted work fulfilment and individuals’ well-being and, as expected, this relationship was mediated by the fulfilment of the hypothesised needs (survival and power, social connection, SDT relationship + autonomy, and SDT competence). The study thus indicates the applicability of the PWT in the South African context. Organisations should thus be encouraged to provide employees with decent work, as this, in turn, will likely increase employees’ work fulfilment and general wellbeing.